The Oxford India Antology of Twelve Modern Indian Poets - Mehrotra, Arvind Krishna (Oxford University)
Contiene poesía de: Nissim Ezekiel, Jayanta Mahapatra, A.K. Ramanujan, Arun Kolatkar, Keki N. Daruwalla, Dom Moraes, Dilip Chitre, Eunice de Souza, Adil Jussawalla, Agha Shahid Ali, Vikram Seth y Manohar Shetty.